2019
DOI: 10.1021/acs.joc.9b00277
|View full text |Cite
|
Sign up to set email alerts
|

A BEt3-Base Catalyst for Amide Reduction with Silane

Abstract: Reported herein is the development of a simple but practical catalytic system for the selective reduction of amides with hydrosilane or hydrosiloxane. Low-cost and readily available triethylborane (1.0 M in THF), in combination with a catalytic amount of an alkali metal base, was found to catalyze the reduction of all three amide classes (tertiary, secondary, and primary amides) to form amines under mild conditions. In addition, the selective transformation of secondary amides to aldimines and primary amides t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…73 Lewis acids accompanied by higher temperature, longer reaction time, and less yield have already been utilized for the dehydration of amides to nitriles. 52,67,74,75 Thus, the authors wanted to study the influence of Lewis acids on the metal-hydride catalytic activity. The significance of a Lewis acid as an additive in the iron-hydride catalytic reaction was extensively studied and it was found that ZnBr 2 was the best under these catalytic conditions.…”
Section: Metal Catalysed Silylative Dehydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…73 Lewis acids accompanied by higher temperature, longer reaction time, and less yield have already been utilized for the dehydration of amides to nitriles. 52,67,74,75 Thus, the authors wanted to study the influence of Lewis acids on the metal-hydride catalytic activity. The significance of a Lewis acid as an additive in the iron-hydride catalytic reaction was extensively studied and it was found that ZnBr 2 was the best under these catalytic conditions.…”
Section: Metal Catalysed Silylative Dehydrationmentioning
confidence: 99%
“…81 Huang and coworkers reported selective reduction of primary amides to nitriles with hydrosilane or hydrosiloxane using a catalytic system triethylborane in combination with an alkali metal base (Scheme 48). 74 They also studied the mechanism of BEt 3 /base catalyzed amide hydrosilylation reaction and found that a modified Piers' silane Si-H⋯B activation mode facilitated the hydride abstraction by BEt 3 by the coordination of the Si-center with a hydroxide or an alkoxide. The reaction proceeded with the hydrosilylation reaction of primary amides using either PhSiH 3 at rt, or polymethylhydrosiloxane (PMHS) at 50°C followed by reduction catalysed by BEt 3 /base.…”
Section: Non-transition Metal Catalyzed Dehydrationmentioning
confidence: 99%
“…25 Very recently, our group has developed a single catalyst [Mn III (O,N,N,O-PLY)Cl] for hydrosilylation of primary amides into amines. 31 Only a few examples of catalytic hydrosilylation of primary amides have been reported to date, 25,[31][32][33] while catalytic deoxygenative hydroboration of primary amides to amines has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, hydride additions to this electron-rich system proved unsuccessful and led us instead to seek a direct, amide-selective reduction of the 1,3-dicarbonyl system. Following a survey of a wide range of existing methods, only Dixon’s reported combination of Vaska’s complex and TMDS was successful in selectively reducing the lactam amide in the presence of both the ketone and very sensitive terminal olefin groups. , …”
Section: Resultsmentioning
confidence: 99%